HIGHER EDUCATION IN NAGALAND: CURRENT STATUS, ROLE, AND CONSTRAINTS - Kikon, Mhabeni (International Journal of Research -GRANTHAALAYAH, 2024)
Higher Education in India is the second largest in the world after China. India has the highest youth population in the world, with 66% of its population under the age of 35. Since a vibrant education system is a prerequisite for nation-building and development, using available data and statistical tools this paper focuses on the role of Higher Education. The paper also attempts to understand key economic development indicators like GER and GPI and how they promote socio-economic status and economic equality in Nagaland.